2018
DOI: 10.1021/acs.jctc.7b00886
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Comparison of Generalized Born Models in the Calculation of Electrostatic Binding Free Energies

Abstract: The need for accurate yet efficient representation of the aqueous environment in biomolecular modeling has led to the development of a variety of generalized Born (GB) implicit solvent models. While many studies have focused on the accuracy of available GB models in predicting solvation free energies, a systematic assessment of the quality of these models in binding free energy calculations, crucial for rational drug design, has not been undertaken. Here, we evaluate the accuracies of eight common GB flavors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 158 publications
(288 reference statements)
0
29
0
Order By: Relevance
“…The specific choice of GB “flavor” depends on one’s needs: a protein folding simulation may call for one flavor of the GB model(84, 79), while a study of a protein in a membrane environment will need quite another(71, 20). The model one may prefer for estimates of ligand binding energies(47), can be different from GB flavors one may recommend for simulations of the DNA(118, 16, 80). Yet a different approach is needed if the molecular charge distribution is described by (polarizable) multipoles, rather than by fixed point charges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific choice of GB “flavor” depends on one’s needs: a protein folding simulation may call for one flavor of the GB model(84, 79), while a study of a protein in a membrane environment will need quite another(71, 20). The model one may prefer for estimates of ligand binding energies(47), can be different from GB flavors one may recommend for simulations of the DNA(118, 16, 80). Yet a different approach is needed if the molecular charge distribution is described by (polarizable) multipoles, rather than by fixed point charges.…”
Section: Discussionmentioning
confidence: 99%
“…(32)] A version of the model, GBNSR6(1, 27) (“Numerical Surface R6 GB”), is available in Amber. It has been tested in calculation of small molecule hydration energies(1) and in protein ligand binding(45), where its accuracy is noteworthy(47).…”
Section: Polar Solvation: the Generalized Born Modelmentioning
confidence: 99%
“…The number densities of presence or number of guest positions in each volume element was defined by a grid [ 36 , 37 ]. There are several generalized Born Models to calculate electrostatic binding free energies [ 40 ], but the electrostatic contribution to is nearly constant inside the cavity ( Figure 1 ) and thus in the trajectories. Moreover the van der Waals term is about times greater than the electrostatic potential energy, making the process of inclusion complex formation essentially dependent on this contribution.…”
Section: Methodsmentioning
confidence: 99%
“…Generally speaking, GB models have shown to be computationally less expensive than the PB models, although the deterioration of the accuracy has always been a concern. Here, we employed a grid-based surface GB model called GBNSR6, 37 which, in a recent study, 38 was shown to be the most accurate among several GB models in terms of the ability to approximate Δ G pol relative to the numerical PB. In this work, Δ G pol is calculated with the ALPB modification 39 , 40 of the generalized Born 41 model: where ϵ in = 1 and ϵ out = 80 are the dielectric constants of the solute and the solvent, respectively, β = ϵ in / ϵ out , α = 0.571412, and A is the electrostatic size of the molecule, which is essentially the overall size of the structure that can be computed analytically.…”
Section: Methodsmentioning
confidence: 99%
“…Generally speaking, GB models have shown to be computationally less expensive than the PB models, although the deterioration of the accuracy has always been a concern. Here, we employed a grid-based surface GB model called GBNSR6, 37 which, in a recent study, 38 was shown to be the most accurate among several GB models in terms of the ability to approximate ∆G pol relative to the numerical PB. In this work, ∆G pol is calculated with the ALPB modification 39,40 of the generalized Born 41 model:…”
Section: Solvation Free Energymentioning
confidence: 99%